Prognostic value of FOXA1 in patients with Т1–2N0M0 breast cancer - R. M. Paltuev; A. G. Kudaybergenova; V. F. Semiglazov; A. V. Komyakhov; A. I. Tseluyko (Опухоли женской репродуктивной системы)
Background. New biomarkers of breast cancer are actively being studied to used them for breast cancer prognosis and develop optimal approaches to therapy. FOXA1 is one of these factors whose prognostic value for breast cancer has been analyzed in several studies.Aim. To evaluate the prognostic value of FOXA1 in patients with T1–2N0M0 breast cancer.Materials and methods. We measured FOXA1 expression in tumor cells of patients with hormone-dependent and hormone-independent breast cancer using the method developed by us (patent No. RU2748716C1 dated 03.06.2020). We performed immunohistochemical examination of tumor tissue using specific antibodies for staining. The Allred scale was used for results interpretation (to assess the number of cells with stained nuclei and the intensity of their staining). Then the total Allred score was calculated and used as a prognostic parameter. Patients with the Allred score between 4 and 8 had a favorable prognosis. We followed up patients in the groups and evaluated their survival. A univariate analysis was used to assess the risk of lethal outcome depending on the level of FOXA1 expression.Results. In 75 % of patients with hormone-dependent and 82 % of patients with hormone-independent breast cancer (stages T1–2, N0 in both groups), the prognostic parameter measured using the Allred scale ranged between 4 and 8 points; their 10-year overall survival was 93 % and 92 %, respectively.Conclusion. Our findings suggest high accuracy of our method for breast cancer prognosis. It can be used for breast cancer prognosis in early stages (T1–2, N0) and expands the range of techniques for breast cancer prognosis.